Sustainable synthesis of renewable surfactants - Goddard, Amy Rose (2016)
This Thesis reports on the synthesis of novel surface active polymers using cyclic esters (D,L-lactide), dicarboxylic acids, oleochemicals and temperature sensitive polyols (D-sorbitol) as renewable building blocks. Product degradability, sustainability and low-toxicity are driving the demand for bio-based polymers and surfactants. Nonetheless, high processing temperatures (≥ 180 °C) and harsh post-reaction treatments are often needed in their synthesis, becoming a barrier to creating materials based on renewable resources.